Statement of the amount of wastage on the Gold and Silver deposits received at the U.S. Branch Mint at San Francisco, and the amount of coinage and parting charges on the same together with the Annual Expenditures from Jan. 1st 1857 to Jan. 1st 1868. - Booth, James Curtis
Tabulation of data including: year, date of settlement, gold wastage, silver wastage, silver excess, coinage charges, total coinage, expenses in [United States] currency, expenses in gold.
Keywords: Gold; Smelting; Silver; Metals--Refining; Mint of the United States; Metallurgy; Silver--Refining; Gold--Refining; Booth, James Curtis, 1810-1888; Old United States Mint (San Francisco, Calif.); United States Mint